Removal of Hematite Water-Based Filter Cake Using Hydrochloric Acid - Osama Siddig; Saad Alafnan; Salaheldin Elkatatny (Geofluids)
The filter cake layer, which is essential to reduce the fluid invasion to the drilled formation, has been reported to be composed mainly of the weighting materials. The complete removal of this layer is recommended to restore the rock permeability. Hematite is one material that is used to create the filter cake. However, the cleanup of hematite-based filter cake has not been studied thoroughly. The objective of the work presented in this paper is to investigate the removal of hematite water-based filter cake using hydrochloric acid. Numerous solubility tests were conducted to study the different factors affecting the treatment of hematite such as temperature and particle size. Based on these results, the treatment duration and acid concentration were selected. The high-pressure high-temperature filtration cell was used to build the filter cake and to soak it in the treatment solution at 100°C. Even though the solubility is increasing with acid concentration, however, no significant improvement was noticed above 12.5 vol.% of HCl. The particle size distribution has a considerable effect on the treatment, and the solubility was found to be 86 wt.% for particles finer than 25 microns and 47 wt.% for particle sizes above 75 microns, all in 10 vol.% HCl. The temperature has a significant influence as the solubility doubled when the temperature increased from 75°C to 100°C. The solubility rate decreased with time and reached the maximum in 16 hours which has been taken as treatment duration. Using 12.5 vol.%, 91 wt.% of the filter cake was successfully removed. In the literature comprehensive study on the cleanup of hematite-based filter cakes is lacking. This research provides new insights into hematite removal and address the different factors that impact the treatment efficiency.